PEMBELAJARAN BERBASIS KARAKTER DI MADRASAH IBTIDAIYAH - Asep Ediana Latip (Jurnal Pendidikan Islam, 2013)
This study aims to determine the level of understanding, implementation and trouble Teachers MI (madrasah) se-Jabodeta (Jakarta-Bogor-Depok-Tangerang) in the character-based learning. The method used was a survey. Samples studied was 10% of the population are selected by cluster sampling technique. The research instrument used was a test and questionnaire. The results showed that 87% of teachers turned a Jabodeta MI-based learning to understand the character. In terms of character-based learning implementation that includes aspects of both the character design and the selection and preparation of assessment, 71% of teachers implement MI Jabodeta a character based learning and have the means to carry it out. The percentage of the total, was 52% of teachers Jabodeta MI as difficult to implement character-based learning, both in the exemplary aspects, monitoring, measurement of success, methods of cultivation of character, the character of the integration process, preparation of instructional design, guide books, and the identification of the value of character.